TINJAUAN PELAKSANAAN ROYA PARTIAL TERHADAP OBJEK HAK TANGGUNGAN - Anggraeni, Lisa; Yunanto, Yunanto; Maharani Sukma, Novira (Magister Kenotariatan Universitas Diponegoro, 2020)
The mortgage right giver who has paid off his obligations to the mortgage right holder, then cancels the mortgage rights on the object of the mortgage right that is charged. Article 22 paragraph (1) of the Underwriting Right Act